Small and Medium Enterprises in the Emerging Economies: Does Entrepreneurial Orientation Matters? - Mohammed, Sani; Bint Abu Talib, Noraini; Hayat Abdu Kohar, Umar (International Journal of Psychosocial Rehabilitation, 2020)
Small and Medium Enterprises (SMEs) are famous for the role they play in the economic development of nations and regions in particular. Hence, the attention of scholars, researchers, and government and non-governmental officials is drawn to it. However, the SMEs in Nigeria suffer serious setbacks, and great failure rates in recent times are noticed. Purpose: The study is purposely to examine the relationship between entrepreneurial orientation (EO) and SME performance in the northeast region of Nigeria, which is known for its high poverty level and general backwardness, coupled with serious insecurity of lives and property due to the activities of Boko Haram. Methodology/materials: The data was collected from a sample of 300 owner/managers of SMEs in Northeast Nigeria using a questionnaire on a Likert scale of 1-10. These data were tested for validity, normality, and common method bias using SPSS. The analysis obtained a 0.089 Cronbach‘s Alpha value and a Kolmogorov value of less than 0.05. Hence, the validity, normality, and the AVE requirement were met. Mean and standard deviation were used to describe the data, and hypotheses were tested using the partial least squares method in SmartPLS 3. Finding: Hypothesis (H1), i.e., innovativeness, was not supported, but the remaining two, proactiveness and risk-taking (H2 and H3), were supported. Implications: This implies that the innovativeness of SMEs in the region does not influence the firm’s performance. But the proactiveness and risk-taking ability of SMEs in the region boost performance. Originality: Most EO studies suggest that environment determines the relationship between EO and SME performance, and interestingly, the overwhelming majority of such studies were concentrated in developed nations. Hence, this current study examines the EO-SMEs performance relationship in the backward-performing region of Nigeria with different environmental backgrounds.